A simple, sensitive and rapid isocratic reversed-phase high-performance liquid chromatography method for determination and stability study of curcumin in pharmaceutical samples - Farjad Amanolahi; Ali Mohammadi; Reza Kazemi Oskuee; Hooriyeh Nassirli; Bizhan Malaekeh-Nikouei (Mashhad University of Medical Sciences, 2017)
Objective: This study was designed to develop and validate a new reversed-phase high-performance liquid chromatography (RP-HPLC) method based on Q2 (R1) International Conference on Harmonization (ICH) guideline for determination of curcumin in pharmaceutical samples. Materials and Methods: The HPLC instrument method was optimized with isocratic elution with acetonitrile: ammonium acetate (45:55, v/v, pH 3.5), C18 column (150 mm×4.6 mm×5 µm particle size) and a flow rate of 1 ml/min in ambient condition and total retention time of 17 min. The volume of injection was set at 20 µl and detection was recorded at 425 nm. The robustness of the method was examined by changing the mobile phase composition, mobile phase pH, and flow rate. Results: The method was validated with respect to precision, accuracy and linearity in a concentration range of 2-100 µg/ml. The limit of detection (LOD) and limit of quantification (LOQ) were 0.25 and 0.5 µg/ml, respectively. The percentage of recovery was 98.9 to 100.5 with relative standard deviation (RSD) < 0.638%. Conclusion: The method was found to be simple, sensitive and rapid for determination of curcumin in pharmaceutical samples and had enough sensitivity to detect degradation product of curcumin produced under photolysis and hydrolysis stress condition.